Usamos nuestra estrategia para realizar estimación - Hermitaño Ruiz, Yanet Susan (2019)
The session entitled “We use our strategy to estimate” is designed for the fourth grade of Primary Education, it was developed in the area of Mathematics._x000D_ In the preparation of the session, we worked with the pedagogical and didactic processes of the area of mathematics to promote meaningful learning._x000D_ The strategies used were designed to promote the active and meaningful participation of all students._x000D_ It is intended at all times to awaken the interest and motivation of the student in mathematics, since it is a very important and valuable area._x000D_ The Introduction is oriented to class planning, performance to be evaluated, evidence of learning and the assessment instrument to be used._x000D_ In the second part the Theoretical Support is developed where the conceptual definitions of the subject to be discussed are exposed, in order to explain in a simple way and with a deep theoretical basis._x000D_ Finally, the third part is dedicated to Pedagogical Support, the foundation of the Mathematics Area according to the new curriculum framework, considering the graduation profile that the student must reach when completing the Regular Basic Education and the approaches that guide the Area in question. In addition to the pedagogical and didactic processes of the area and the evaluation techniques and instruments.